Effects of Tranexamic Acid Based on its Population Pharmacokinetics in Pediatric Patients Undergoing Distraction Osteogenesis for Craniosynostosis: Rotational Thromboelastometry (ROTEM(TM)) Analysis - Kim, Eun Jung (Int J Med Sci, 2018)
Background: Distraction osteogenesis for craniosynostosis is associated with significant hemorrhage. Additionally, patients usually require several transfusions. Tranexamic acid (TXA) is effective for reducing blood loss and the need for transfusions during surgeries. However, the significance of TXA infusion has not been thoroughly described yet. Methods: Forty-eight children undergoing distraction osteogenesis for craniosynostosis were administered intraoperative TXA infusion (loading dose of 10 mg/kg for 15 min, followed by continuous infusion at 5 mg/kg/h throughout surgery; n = 23) or normal saline (control, n = 25). Rotational thromboelastometry (ROTEM(TM)) was conducted to monitor changes in coagulation perioperatively. Results: Blood loss during surgery was significantly lower in the TXA-treated group than it was in the control group (81 vs. 116 mL/kg, P = 0.003). Furthermore, significantly fewer transfusions of red blood cells and fresh frozen plasma were required in the TXA group. In the control group, clotting time during the postoperative period was longer than it was during the preoperative period. Similarly, clot strength was weaker during the postoperative period. D-dimer levels dramatically increased in the control group compared with the TXA group after surgery. The duration of mechanical ventilation and the number of postoperative respiratory-related complications were significantly greater in the control group than they were in the TXA group. Conclusions: TXA infusion based on population pharmacokinetic analysis is effective in reducing blood loss and the need for transfusions during the surgical treatment of craniosynostosis. It can also prevent the increase in D-dimer levels without affecting systemic hemostasis.